Adaptive Interference Restriction Among Spatial Streams Based on Difference in Singular Values for PAPR Reduction in Uplink Eigenmode Massive MIMO Transmission - Yuta Abekura; Takanori Hara; Satoshi Suyama; Satoshi Nagata; Kenichi Higuchi (IEEE Access)
In this paper, we propose two peak-to-average power ratio (PAPR) reduction methods that apply adaptive in-band interference restriction based on singular value differences between spatial channels in uplink eigenmode massive multiple-input multiple-output (MIMO) transmission. In uplink transmission utilizing high-frequency bands, reducing PAPR is crucial to suppress non-linear distortion and ensure sufficient transmission distance, given the stringent amplification requirements of power amplifiers. Therefore, the proposed methods direct the PAPR reduction signals caused by clipping and filtering (CF) only to spatial channels with relatively small singular values, thereby avoiding in-band interference in spatial channels with larger singular values, which are more susceptible to such interference compared to the case without PAPR reduction. After that, the two proposed methods restrict PAPR reduction signals for all or a subset of subcarriers based on the transmission quality requirements. Both interference restrictions allow for more effective PAPR reduction while tolerating interference in the data streams. Computer simulations demonstrate that the transmission quality of the proposed methods is improved by up to approximately 30% compared to the case without PAPR reduction. Moreover, a comparative evaluation of the two proposed methods demonstrates that the interference restriction across all subcarriers effectively mitigates in-band interference caused by the resulting PAPR reduction signals while reducing the PAPR.